2013
DOI: 10.1172/jci64721
|View full text |Cite
|
Sign up to set email alerts
|

Congenital amegakaryocytic thrombocytopenia iPS cells exhibit defective MPL-mediated signaling

Abstract: Congenital amegakaryocytic thrombocytopenia (CAMT) is caused by the loss of thrombopoietin receptormediated (MPL-mediated) signaling, which causes severe pancytopenia leading to bone marrow failure with onset of thrombocytopenia and anemia prior to leukopenia. Because Mpl -/-mice do not exhibit the human disease phenotype, we used an in vitro disease tracing system with induced pluripotent stem cells (iPSCs) derived from a CAMT patient (CAMT iPSCs) and normal iPSCs to investigate the role of MPL signaling in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 58 publications
1
44
0
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14] These mouse-based observations are consistent with the megakaryocytic and thrombocytic components of the human CAMT disorder, 30 where disease severity correlates with degree of failure of THPO/MPL signaling. 5,31,32 However, an outstanding inconsistency was that, although CAMT patients can present with TP as neonates, 5,31 the disease could also progress within the first year of life.…”
Section: Introductionsupporting
confidence: 58%
“…[6][7][8][9][10][11][12][13][14] These mouse-based observations are consistent with the megakaryocytic and thrombocytic components of the human CAMT disorder, 30 where disease severity correlates with degree of failure of THPO/MPL signaling. 5,31,32 However, an outstanding inconsistency was that, although CAMT patients can present with TP as neonates, 5,31 the disease could also progress within the first year of life.…”
Section: Introductionsupporting
confidence: 58%
“…We have developed a coculture system with which human ESCs or iPSCs can be differentiated into multipotent hematopoietic progenitors capable of yielding megakaryocytes, erythroblasts, or lymphocytes [21][22][23]27]. Using this culture system, we first sought to generate erythroblasts from the H1 and KhES-3 hESC lines using the protocol diagrammed in Figure 1A and from human CB-CD34 + cells using the protocol diagrammed in Figure 1B.…”
Section: Optimization Of Cell Fixation For Tracing Expression Of Indimentioning
confidence: 99%
“…In addition, we considered the diagnosis of AATP and PRCA based on the results of a bone marrow examination, which revealed the complete absence of megakaryocytes and erythro- Recently, Hirata et al analyzed induced pluripotent stem cells derived from a patient with CAMT and demonstrated that MPL signaling is indispensable for the maintenance of MPPs and for the transition from MPPs to MEPs during early hematopoiesis. The absence of functional MPL leads to deficiencies in both erythropoiesis and megakaryopoiesis, although some development of myeloid cells is retained (4). These reports suggested the possibility that, in our case, the inhibitory effect of anti-c-Mpl antibodies on MEP proliferation occurred due to the total absence of both megakaryocytes and erythroblasts.…”
Section: Discussionmentioning
confidence: 55%
“…TPO receptor c-Mpl is expressed on hematopoietic stem cells (HSCs) and progenitor cells (HPCs) (3). TPO/MPL signaling plays an important role in the maintenance and regulation of HSCs and is indispensable for the maintenance of multipotent progenitors (MPPs) and their transition to common megakaryocyte-erythrocyte progenitors (MEPs) (4). To the best of our knowledge, this is the first report of a patient with (probable) pure red cell aplasia (PRCA) with acquired amegakaryocytic thrombocytopenic purpura (AATP), a rare disorder that is characterized by thrombocytopenia causing the total absence or a marked reduction of megakaryocytes in the bone marrow (5), and which is associated with anti-cMpl antibodies.…”
Section: Introductionmentioning
confidence: 99%